Medicament testing on acupuncture points as a non-invasive diagnostic tool for determining the daily doses of sofosbuvir in patients with chronic hepatitis C virus infection - Naylya Djumaeva; Gulnara Akhundjanova; Leyla Djumaeva; Dilbar Urunova (SpringerOpen, 2023)
Abstract Background Acupuncture points are known for their unique bioelectric properties. Medication testing at acupuncture points has not previously been used to determine the daily doses of sofosbuvir in patients with chronic hepatitis C virus infection. Results This pilot study included 61 patients with a confirmed diagnosis of chronic hepatitis C virus infection. Medicament testing of acupuncture points of the liver meridian ("Xing-jian") and Voll's circulation meridian ("Cells and lobules of the liver") was performed to determine the daily doses of sofosbuvir. A correlation analysis was carried out between the tested doses of the drug and the viral load in the blood of patients to confirm the results of testing the daily doses of sofosbuvir. Patients with chronic hepatitis C virus infection showed a significant positive correlation between tested daily doses of sofosbuvir and viral load in their blood. The mean values of the tested doses of sofosbuvir did not vary at different acupuncture points and significantly differed depending on viral load. Conclusions This study showed that acupuncture points can serve as a diagnostic tool in the process of medicament testing and allow the determination of daily doses of sofosbuvir in patients with chronic hepatitis C virus infection. To further assess the clinical applications and physiological basis of medicament testing methods, additional clinical and instrumental studies are needed with a large sample of patients.